THE MECHANISM OF FINANCIAL PLANNING THROUGH THE PRISM OF ENSURING THE EFFICIENCY OF BUSINESS ENTITIES - KUCHYN, Anton (Scientific journal «World of Finance», 2023)
Introduction. The financial stability, profitability and development of business entities are the hallmarks of an efficient business, which requires a long-term development plan. Although the development strategy of business entities cannot take into account all possible options for improving the financial position in different periods of time, financial planning for different timeframes and in specific conditions helps to ensure that costs and revenues are managed at the level of the business entity. The avoidance of structural deficiencies in the economy is possible due to complete and large-scale planning. Therefore, outlining financial planning under martial law is important not only from a theoretical but also from a practical point of view.The purpose of the article is to determine the principles of financial planning of business entities under martial law.Results. The essence of financial planning is considered and the criteria for assessing the effectiveness of financial planning of business entities by the objects of assessment (liquidity, business activity, financial stability, and financial risks) are determined. The prerequisites and problems of financial planning of business entities under martial law are outlined. The tasks of financial planning of business entities under martial law are developed, including ensuring effective directions for the formation and use of financial resources, finding reserves to increase revenues, assessing the performance of heads of responsibility centres, assessing the quality of financial plans, etc.Conclusions. It is substantiated that financial planning should be understood as a purposeful process of developing development plans and financial planning (regulatory) parameters with a view to providing an economic entity with the necessary financial resources to form the efficiency of its economic and financial activities in the current and strategic perspective. The author systematizes the problems of formation and implementation of financial planning of business entities in the context of external (military actions and crisis phenomena in the economy, variability of tax legislation) and internal problems (inaccuracy of indicators of financial plans, inability to use borrowed funds, refusal to make a profit, lack of financial and material resources, incompetence of personnel in financial planning and lack of use of software solutions for financial planning).